Ecclesiastical Asset Management and the New Introduction Of Section 2b of the Value Added Tax Act - Blankenberg, Mike (Archives of Business Research, 2021)
This paper deals with church assets and the changes in the German VAT law with the resulting consequences. The implementation of EU law has resulted in numerous changes in the handling of assets and commercial facilities of institutional bodies such as the church. Using the example of the church district administration of the Evangelical Lutheran Church District of Dithmarschen, an overview of the application cases for assets was examined. After an introductory overview and an analytical examination of the new law in the value added tax law, a result of action is provided in this elaboration, which will also be of interest for comparable facilities, corporations and institutions.